Beyond Relevance: How Perceived Difficulty Shapes Veterinary Students' ESP Reading Comprehension - Wibowo, Amiruddin Hadi; Ulfaika , Romlah; Wirawati, Bekti; Panggalih , Wahyun Bardianing; Suryarini , Diah Yovita (Reforma: Jurnal Pendidikan dan Pembelajaran, 2025)
This study examines veterinary students’ perceptions and reading comprehension of English for Specific Purposes (ESP) texts in veterinary science. The subjects were 60 undergraduate veterinary students who participated in the study by responding to a 20-item questionnaire that assessed four dimensions: relevance, perceived difficulty, reading strategies, and text format. The students also completed an eight-item reading comprehension test based on authentic veterinary texts. The findings showed that students generally held positive perceptions toward the ESP materials, particularly in terms of text format and support, while still acknowledging linguistic challenges related to vocabulary and sentence structure. The average reading comprehension score was 5.5 out of 8, indicating a moderate level of understanding. Correlation analysis revealed weak but statistically significant positive relationships between perceptions of relevance (r = 0.26, p < .05) and difficulty (r = 0.28, p < .05) with reading comprehension performance. These results highlight that while veterinary students recognize the importance of ESP reading materials, pedagogical interventions are necessary to enhance comprehension outcomes. The study underscores the importance of scaffolding techniques, vocabulary support, and structured pre-reading activities in ESP courses for veterinary students.ed pre-reading activities in ESP courses for veterinary students